THE IMPACT OF ONLINE TRAINING DURING THE COVID-19 PANDEMIC ON THE STRENGTH ENDURANCE OF FEMALE COLLEGE STUDENTS - P. Petkov (Trakia Journal of Sciences)
The years of the COVID-19 pandemic (2020 -2022) are unparalleled in modern human history. Isolation has further immobilized individuals and further impaired their physical fitness. The aim of the present study was to determine the level of strength endurance of female students after the COVID-19 pandemic and compare it with that before it. To realize the objective, we set the following tasks: to develop a test battery, to perform testing, to process and analyze the data of the testing. Research methods: testing, analysis of variance, comparative analysis, graphical method. The testing was conducted during the winter semester of the academic year 2022/2023. The contingent of the study were 67 female students with the average age of 20-24 years from Faculty of Agriculture, Faculty of Veterinary Medicine and Faculty of Economics at Trakia University, Sofia. The study population consisted of students from the study population of the University of Stara Zagora. The same test battery was administered to female students of Trakia University before the pandemic in 2017. We compare the results of female students before and after the pandemic from COVID-19. The test battery included the following tests: vis to failure, 2 kg dumbbell hold, plank, push-ups from knees to failure, abdominal crunches to failure. After the analyses of the tests performed, we concluded that the COVID-19 pandemic and the subsequent immobilization affected the strength endurance of the female students by decreasing it.